The diversity of Cordycepioid fungi (Ascomycotina : Clavicipitales) reported from Nepal - Adhikari, M. K. (Journal of Plant Resources, 2008)
This paper provides an up dated checklist of diversity of Cordycepioid fungi (Cordyceps and its allied species) reported from Nepal. A key for identification to generic level, the distribution of species, the medicinal value and current approach of forest regulation for their collection, trade and transit have been provided. Two species viz. Isaria nipponica Kobayasi and Isaria tenuipes Peck are added as new records to the knowledge on the Cordycepioid allied species from Nepal. This group falls under 21 species, 6 genera and 3 families. Among them one species is reported as endemic to Nepal. Bulletin of the Department of Plant Resources Vol 30, 2008 pp 1-8